KOREKSI KESESUAIAN LAHAN DENGAN REFERENSI KESESUAIAN SUHU PERTANAMAN KENTANG MERAH PADA DATARAN SEDANG BENGKULU - Muhammad Faiz Barchia; S Nur Muin; Mukhtasar .; N C Deta (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACTAdaptation red potato planted on medium altitude in Bengkulu upland in order to correct land suitability classification based on criteria of land characteristics/quality. The research was conducted from July to October 2009, Kepahiang, Bengkulu located in 4 (four) experimental stations; mediumaltitude which located in Kelobak 525 m (up sea level, usl) and Pematang Donok, 650 m usl comparing location in Tugu Rejo 1135 m usl and Bandung Baru 1346 usl. Temperature in high altitude on Bengkulu upland was 22.3 oC in Bandung Baru and 23.5 oC in Tugu Rejo. In highland Bengkulu, land suitability class was Marginally Suitable (S3t) around Bandung Baru, while around Tugu Rejo, and medium altitude of upland Bengkulu around Kelobak and Pematang Donok with average temperature 24.8 oC categorized Permanently Non Suitable (N2t). Following the result of red potato adaptation research, there was no significantly diference among 4 (four) experimental location of potato yields in which yield of potato in Bandung Baru was 16.7 tons ha-1, Tugu Rejo was 15.5 ton ha-1, and yield of red potato in medium altitude of Bengkulu upland in Kelobak was 15.4 tons ha-1 and Pematang Donok was 19.3 tons ha-1. Based on those, temperature as a limiting factor for potato growth was the same suitable for red potato cultivation in the high and medium altitude of Bengkulu upland. Criteria of land sutability classification for potato cultivation in medium altitude of Bengkulu upland categorized N2t, Permanently Unsuitable should be corrected because of medium altitude of upland in Bengkulu high potential to develop as area for red potato cultivation.Key words: temperature, land suitability classification, red potato.